Football teams for people with intellectual disabilities living in the community: "it helps your self-esteem and that, don't it?". Issue 4 (11th December 2017) - White, Rose; Lister, Katherine; Northend, Kristian; Moore, Stephen; Rayner, Kelly
Abstract : Purpose: People with intellectual disabilities (ID) can be vulnerable to developing mental health problems. It has been found that participating in regular exercise can help to improve emotional well-being, both in typically developing people and those with ID. The purpose of this paper is to investigate the experiences of community clients with ID who have engaged in a football training programme, and the perceived impacts on attitudes, mood and behaviour. Design/methodology/approach: Interviews with seven patients from generic or forensic community ID services were conducted. The transcripts were analysed using interpretative phenomenological analysis. Findings: Two master themes were identified from the interviews, "Striving" and "Togetherness". Originality/value: The most important factors related to taking part in the football programme were the social, emotional and personal growth associated with being part of a team and general enjoyment of being part of something. Although aspects of football knowledge and physical fitness were still evident, their impact seemed to be less significant. The experience of football was overwhelmingly positive.